Introduction Of Indonesian Traditional Clothes in The Multicultural-Based Pancasila Student Profile Strengthening Project In SMKN 2 Tangerang City - Rahayu, Bening Mujianti; Muhyidin, Asep; Leksono, Suroso Mukti; Jamaludin, Ujang (Literasi: Jurnal Ilmu Pendidikan, 2024)
Multicultural education in Indonesia should be a means to promote the values of tolerance and respect for ethnic, cultural, racial, religious and linguistic differences. The application of the introduction of traditional clothing by means of contests or parades between classes makes not only students gain insight between cultural diversity and traditional clothing, but teachers and other staff will also gain insight and also increase interest in cultural diversity in Indonesia. This research aims to introduce diversity and diversity about traditional clothing in Indonesia as a wealth of Indonesian culture which is implemented in the subject of Pancasila and Citizenship Education. This research was conducted using descriptive qualitative methods, with data collection techniques through observation, interviews and documentation. The results showed that a positive impact occurred after the introduction of traditional clothing contest, namely an increased sense of tolerance, increased insight, the learning and teaching process was more interactive and not boring for students and teachers. The quality of multiculturalism education indirectly increases with the existence of learning media to strengthen the profile of Pancasila students by introducing traditional clothing to SMKN 2 Tangerang for multiculturalism education in accordance with the vision of Pancasila education in Indonesia.Keywords: Multiculturalism, Bhinneka Tunggal Ika, P5 Project, Indonesian Traditional Clothes.